Entrepreneurship, Innovation and Institutions - Erik Stam; B. Nooteboom (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2011)
This paper discusses the nature of entrepreneurship and its relation to innovation along a cycle in which exploration and exploration follow upon each other. We place the roles of entrepreneurship in innovation policy within this cycle of innovation. Different types of innovation along the cycle of innovation are realized with different forms of entrepreneurship, which are constrained or enabled by different legal institutions. One of the key roles of governments is to design, change or destruct institutions in order to improve societal welfare. The question is what governments should do in the context of innovation policy. Here, social scientists can make a contribution by providing insight into what entrepreneurship and innovation is (theories about these phenomena), and how institutions affect them in reality (empirical evidence about their effects). This requires social scientists to be engaged scholars and to provide new policy options as an honest broker between the academic world and the policy world. The key question of this paper is: How can policy best enable innovation based entrepreneurship? The answer is derived from looking at both theoretical tenets and empirical evidence using an institutional design perspective, which aims at providing arguments for the design, change and/or destruction of institutions, given the goals of the governments. We provide an overview of some (empirically tests of) institutions that enable or restrain particular types of entrepreneurship. Examples of these institutions are intellectual property rights and the Small Business Innovation Research program, employment protection, and non-compete covenants.
Keywords: 330; entrepreneurship; innovation; institutions; innovation policy